PENERAPAN METODE DISCOVERY LEARNING BERBANTUAN MEDIA GAMBAR PADA PEMBELAJARAN DARING MENULIS TEKS PROSEDUR - Enden Putri Kusumawaty; Ika Mustika; Alfa Mitri Suhara (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The idea of ​​this research was initiated by the fact that there are still many students who have difficulty determining ideas and ideas in producing a review text by selecting the structure and language of the text. The Project-Based Learning learning model is an alternative solution to the learner-centred learning model, namely a learning model that uses projects or activities as a learning tool to achieve attitude, knowledge and skill competencies. Therefore, this research was conducted to determine the learning process and the impact of the student's ability to write review texts. The purpose of the research is to determine the ability to write a review text of students using the Project-Based Learning learning model assisted by Wattpad. The research method used in this research is descriptive qualitative which only has one cycle of processing, data collection and data processing. The results showed that nineteen students got a high score, six students got an adequate score, and one student got a low score. The results of the study can be said that using the Project-Based Learning model can positively affect the learning process and improve students' skills in writing review texts.